Determination of chloride in admixtures and aggregates for cement by a simple flow injection potentiometric system - Jaroon Junsomboon (2018)
A simple flow injection system using three 3-way solenoid valves as an electric control injection valve and with a simple home-made chloride ion selective electrode based on Ag/AgCl wire as a sensor for determination of water soluble chloride in admixtures and aggregates for cement has been developed. A liquid sample or an extract was injected into a water carrier stream which was then merged with 0.1 M KNO3 stream and flowed through a flow cell where the solution will be in contact with the sensor, producing a potential change recorded as a peak. A calibration graph in range of 10-100 mg L-1 was obtained with a detection limit of 2 mg L-1. Relative standard deviations for 7 replicates injecting of 20, 60 and 90 mg L-1 chloride solutions were 1.0, 1.2 and 0.6%, respectively. Sample throughput of 60 h-1 was achieved with the consumption of 1 mL each of electrolyte solution and water carrier. The developed method was validated by the British Standard methods. © 2008 Elsevier B.V. All rights reserved.